2018
DOI: 10.3390/ijerph15050899
|View full text |Cite
|
Sign up to set email alerts
|

Water-Based Automobile Paints Potentially Reduce the Exposure of Refinish Painters to Toxic Metals

Abstract: Exposure to lead-containing dusts is a global public health concern. This work addresses an important issue of whether eco-friendly water-based paints reduce the exposure potential of auto-repainting workers to metals. With this aim, metal levels in automobile paints and worker metal exposure were measured using both solvent- and water-based paints. The levels of metals, and particularly Pb, Cr (total), Fe, and Cu, in solvent-based paints varied greatly among colors and brands. Lead concentrations ranged from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The high Cu level in the Sidi Haider station of up to 150 mg/kg is due to the presence of this auto box; Several studies have proven the relationship between Cu levels and certain polluting sources (paint, brake pads, tires, and car wiring) (Winther and Slento 2010;Hsu et al 2018;Barbosa et al 2020).…”
Section: Discussionmentioning
confidence: 97%
“…The high Cu level in the Sidi Haider station of up to 150 mg/kg is due to the presence of this auto box; Several studies have proven the relationship between Cu levels and certain polluting sources (paint, brake pads, tires, and car wiring) (Winther and Slento 2010;Hsu et al 2018;Barbosa et al 2020).…”
Section: Discussionmentioning
confidence: 97%
“…The emphasis on pollution risk arises from the use of solvent-based coatings. To address this, there is a growing interest in exploring eco-friendly alternatives, like water-based paints, which aim to minimize the emission of harmful chemicals during the automotive painting process, fostering a more sustainable and environmentally conscious approach [15]. The shift towards water-based and powder coating technologies has presented itself as a more environmentally friendly alternative.…”
Section: Environmental Impact and Technological Innovations In Automo...mentioning
confidence: 99%
“…Another study demonstrated that the use of appropriate personal protective equipment and good workplace hygiene were associated with reduced risk of symptoms of neurotoxicity in solvent-exposed vehicle spray painters (Keer et al, 2018). A Taiwanese study concluded that waterborne paints reduce the exposure potential to lead and other toxic metals (except copper) (Hsu et al, 2018). Information is available showing health impacts from VOC exposures to workers in other occupations (Hasana et al, 2013).…”
Section: Social Impact Evaluationmentioning
confidence: 99%